Soft magnetic metal powders, magnetic cores, magnetic components and electronic devices
Patent Information
- Application Number
- CN202610529880.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-25
- Filing Date
- 2026-04-21
- Publication Date
- 2026-10-27
AI Technical Summary
[0008]发明所要解决的技术问题
Smart Images

Figure CN122991794A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to soft magnetic metal powder, magnetic core, magnetic components, and electronic devices. Background Technology
[0002] Patent Document 1 describes a magnetic core using a composite magnetic material, which is obtained by mixing iron-based crystalline alloy magnetic powder and iron-based amorphous alloy magnetic powder to obtain a mixed magnetic powder, and further mixing an insulating binder material therein.
[0003] Patent document 2 describes an inductor using a composite magnetic material, which is obtained by mixing Fe-Ni alloy magnetic powder with hard amorphous alloy magnetic powder to obtain a mixed magnetic powder, and then coating each particle contained therein with a thermosetting resin.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent Application Publication No. 2004-197218
[0007] Patent Document 2: Japanese Patent Application Publication No. 2004-363466 Summary of the Invention
[0008] The technical problem that the invention aims to solve
[0009] The purpose of this invention is to provide a soft magnetic metal powder whose voltage resistance is difficult to decrease even when formed under high pressure.
[0010] Technical solutions for solving technical problems
[0011] To achieve the above objectives, the soft magnetic metal powder of the present invention comprises soft magnetic metal particles having a core and a coating portion, wherein...
[0012] The aforementioned soft magnetic metal particles contain Fe.
[0013] The aforementioned coating portion has an oxide layer in contact with the surface of the aforementioned core portion.
[0014] The oxide layer described above has a second layer in contact with the surface of the core portion and a first layer in contact with the second layer.
[0015] The first and second layers described above contain oxides of the elements contained in the core.
[0016] When observing the cross-section of the soft magnetic metal particles using HAADF-STEM, the first layer exhibits a more uneven brightness distribution compared to the second layer.
[0017] This could be achieved by binarizing the image obtained from observing the cross-section of the aforementioned soft magnetic metal particles using HAADF-STEM into high-brightness and low-brightness regions.
[0018] When the area ratio of the high-brightness region in the first layer is set to S1 and the area ratio of the high-brightness region in the second layer is set to S2, S1 < S2.
[0019] It could be: satisfying 0.02≤S1≤0.98.
[0020] The thickness of the oxide layer can be less than 200 nm.
[0021] The aforementioned covering portion may have a coating layer that is in contact with the surface of the aforementioned oxide layer.
[0022] The magnetic core of the present invention comprises the above-mentioned soft magnetic metal powder.
[0023] The magnetic component of the present invention comprises the aforementioned soft magnetic metal powder.
[0024] The electronic device of the present invention comprises the above-described soft magnetic metal powder. Attached Figure Description
[0025] Figure 1 This is a schematic diagram of the cross-section of a soft magnetic metal particle.
[0026] Figure 2 This is an example of a chart obtained through X-ray crystal structure analysis.
[0027] Figure 3 In order to pass through Figure 2 An example of a pattern obtained by contour fitting of a chart.
[0028] Figure 4 This is a HAADF-STEM image of the cross-section of a soft magnetic metal particle.
[0029] Figure 5 To pick Figure 4 A portion of the image.
[0030] Figure 6 To Figure 5 The image obtained by binarization.
[0031] Figure 7 In order to be in Figure 6 The image contains two imaginary lines.
[0032] Figure 8 This is a cross-sectional schematic diagram of the powder coating device. Detailed Implementation
[0033] Hereinafter, the soft magnetic metal powder and the like according to embodiments of the present invention will be described.
[0034] The magnetic core of this embodiment contains soft magnetic metal powder as a magnetic material.
[0035] Furthermore, the magnetic core may contain resin. There are no particular restrictions on the type and content of the resin. Examples of resin types include thermosetting resins such as phenolic resin and epoxy resin. The resin content relative to the magnetic powder can be more than 1% by mass and less than 5% by mass.
[0036] exist Figure 1 The diagram shows a cross-sectional view of the soft magnetic metal particles 1 contained in the soft magnetic metal powder. (See diagram below.) Figure 1 As shown, the soft magnetic metal particle 1 has a core portion 2 and a coating portion 10.
[0037] (Core 2)
[0038] There are no particular restrictions on the composition of the core 2, as long as the core 2 is composed of a soft magnetic metal. For example, the core 2 can be composed of an iron-based soft magnetic metal, wherein the total amount of Fe, Co and Ni is 70 at% or more, and the proportion of Fe relative to the total amount of Fe, Co and Ni is 50 at% or more.
[0039] By making the core 2 a soft magnetic iron metal, it is easy to reduce the coercivity Hc of the magnetic core and increase the relative permeability of the magnetic core.
[0040] Typically, the core 2 is significantly larger than the coating 10. In fact, the composition of the soft magnetic metal powder, the soft magnetic metal particles 1, and the core 2 can be considered to be completely identical.
[0041] There are no particular restrictions on the composition of soft magnetic metal powders. For example, compositions that readily exhibit amorphous structures can be listed, such as Fe-Co-B-P-Si-Cr systems, Fe-Co-B-P-Si-Cr-C systems, Fe-Si-B systems, Fe-Si-B-C systems, Fe-Si-B-C-Cr systems, Fe-Co-P-C systems, Fe-Co-B systems, and Fe-Co-B-Si systems. Furthermore, compositions that readily exhibit nanocrystalline structures can be listed, such as Fe-Si-B-Nb-Cu systems, Fe-B-Nb-P systems, Fe-Si-B-Nb-P systems, Fe-Co-B-P-Si systems, and Fe-Co-B-P-Si-Cr systems. Other examples include compositions that readily possess a crystalline structure, such as the Fe-Si system, Fe system, Fe-Ni system, Fe-Si-Cr system, Fe-Si-Al system, Fe-Si-Al-Ni system, Fe-Ni-Si-Co system, Fe-Co system, Fe-Co-V system, Fe-Co-Si system, and Fe-Co-Si-Al system.
[0042] When the soft magnetic metal powder contains Fe, Co, Ni, and / or Si, the combined content of Fe, Co, and Ni relative to all elements contained in the soft magnetic metal powder can be 70 at% or more and 100 at% or less, and the content of Fe relative to the combined content of Fe, Co, and Ni can be 50 at% or more and 100 at% or less. The content of Si relative to all elements contained in the soft magnetic metal powder can be greater than 0 at% and less than 20 at% or less. Furthermore, the combined content of other elements relative to all elements contained in the soft magnetic metal powder can be 0.1 at% or more and less than 20 at% or less.
[0043] The soft magnetic metal particle 1 can have the following composition, namely, in terms of atomic ratio, it consists of the following composition formula: constitute,
[0044] X1 is selected from one or more of Co and Ni.
[0045] X2 is selected from one or more of the following elements: Al, Mn, Ag, Zn, Sn, As, Sb, Cu, Cr, Bi, N, O, S, and rare earth elements.
[0046] M is selected from one or more of Nb, Hf, Zr, Ta, Mo, W, Ti, and V.
[0047] 0≤a≤0.150,
[0048] 0≤b≤0.200,
[0049] 0≤c≤0.200,
[0050] 0≤d≤0.200,
[0051] 0≤e≤0.200,
[0052] 0.100≤a+b+c+d+e≤0.300,
[0053] α≥0,
[0054] β≥0,
[0055] 0≤α+β≤0.50.
[0056] With a composition within the above range, the coercivity of the magnetic core is easily reduced, and the relative permeability of the magnetic core is easily increased.
[0057] The soft magnetic alloy particle 1 (core 2) may also contain elements other than those mentioned above (i.e., elements other than Fe, X1, X2, M, B, P, Si, and C) as unavoidable impurities. For example, it may contain less than 0.1% by mass of unavoidable impurities.
[0058] There are no particular restrictions on the microstructure of the core 2. It can be a structure composed of amorphous materials, nanocrystals, or crystals.
[0059] The term "structure composed of amorphous material" refers to a structure with an amorphization rate X of 85% or higher. Structures containing crystals within an amorphization rate of 85% or higher are considered structures composed of amorphous material. Structures composed of amorphous material include structures composed almost entirely of amorphous material and structures composed of heteroamorphous material. The term "structure composed of heteroamorphous material" refers to a structure containing crystals within an amorphous material. In the case of heteroamorphous structures, the average crystal grain size of the crystals present in the amorphous material can be 0.1 nm or more and 10 nm or less. The term "structure composed of nanocrystals" refers to a structure with an amorphization rate X of less than 85% and an average crystal grain size of less than 100 nm. The average crystal grain size of the crystals in a nanocrystal structure can be 3 nm or more and 50 nm or less. The term "structure composed of crystals" refers to a structure with an amorphization rate X of less than 85% and an average crystal grain size greater than 100 nm. The average crystal grain size can be confirmed by observing the cross-section of core 2 using STEM.
[0060] The amorphization rate X can be determined by X-ray crystal structure analysis using XRD, or by EBSD (electron spectroscopy) or electron diffraction. The method for determining it using XRD is described below.
[0061] The amorphization rate X of soft magnetic metal powder is represented by the following formula (1).
[0062]
[0063] Ic: Crystal scattering integral intensity.
[0064] Ia: Integral intensity of amorphous scattering.
[0065] Regarding the amorphization rate X, X-ray crystal structure analysis of soft magnetic metal powder is performed by XRD, and the phase is determined. The peak values of crystallized Fe or compounds (Ic: crystal scattering integral intensity, Ia: amorphous scattering integral intensity) are read, and the crystallization rate is obtained based on the peak intensity. The calculation is then performed using the above formula (1). The calculation method is explained in more detail below.
[0066] X-ray crystal structure analysis of soft magnetic metal powder was performed using XRD. The results were as follows: Figure 2 The graph shown is used. The contour is fitted using the Lorentz function of equation (2) below, resulting in the graph shown below. Figure 3 The crystal composition pattern α shown represents the integrated intensity of crystal scattering. c α represents the amorphous composition pattern representing the integral intensity of amorphous scattering. a and the pattern α that combines them c+a The amorphization rate X is obtained by using the above equation (1) based on the integrated intensity of crystalline and amorphous scattering of the obtained pattern. Furthermore, the measurement range is set to the range where the diffraction angle 2θ = 30° to 60° from the amorphous halo can be confirmed. Within this range, the error between the integrated intensity measured by XRD and the integrated intensity calculated using the Lorentz function is kept within 1%.
[0067]
[0068] Where h: peak height, u: peak position, w: half-peak width, b: background height.
[0069] There are no particular limitations on the average particle size of the soft magnetic metal powder 1. For example, it can be greater than 1 μm and less than 100 μm. When using soft magnetic metal powder 1 with a small average particle size, the withstand voltage can be easily increased, and the deviation of the withstand voltage can also be easily reduced.
[0070] (Covering part 10)
[0071] The soft magnetic metal particle 1 in this embodiment has a coating portion 10 that contacts the surface of the core portion 2. For example... Figure 1As shown, the coating portion 10 has at least an oxide layer 11 in contact with the surface of the core portion 2. Furthermore, the oxide layer 11 has a second layer 11b in contact with the surface of the core portion 2, and a first layer 11a in contact with the second layer 11b. Both the first layer 11a and the second layer 11b contain oxides of the elements contained in the core portion 2.
[0072] When the core 2 contains Fe and Si, the second layer 11b may contain oxides of Fe and / or oxides of Si. The oxides of Fe may be simple oxides of Fe or complex oxides containing Fe. The oxides of Si may be simple oxides of Si or complex oxides containing Si.
[0073] In contrast, the first layer 11a may primarily contain Fe oxides. The Fe oxides may be simple Fe oxides or Fe-containing complex oxides.
[0074] The proportion of Si in the first layer 11a can be less than the proportion of Si in the second layer 11b. For example, if the proportion of Si in the first layer 11a is set as Si1 and the proportion of Si in the second layer 11b is set as Si2, then Si1 < Si2.
[0075] When observing the cross-section of the soft magnetic metal particle 1 using HAADF-STEM, the first layer 11a has a more uneven brightness distribution compared to the second layer 11b.
[0076] The HAADF-STEM image obtained by observing the cross-section of soft magnetic metal particle 1 using HAADF-STEM is shown below. Figure 4 In the middle. For example Figure 4 As shown, the soft magnetic metal particle 1 has an oxide layer 11 in contact with the surface of the core 2. It also has a coating layer 13 in contact with the surface of the oxide layer 11. The coating layer 13 will be described below. Furthermore, in contact with the surface of the coating layer 13 is a Pt deposition layer attached to the surface of the soft magnetic metal particle 1 for observation using HAADF-STEM.
[0077] Figure 5 It's enlarged. Figure 4 The portion of the diagram enclosed by a thick dashed line. (Example) Figure 5 As shown, the first layer 11a has a more uneven brightness distribution compared to the second layer 11b.
[0078] in addition, Figure 6 Yes Figure 5 The image obtained by performing Otsu binarization (hereinafter referred to as binarization) on the high-brightness and low-brightness regions. Based on... Figure 6It can be seen that the second layer 11b has a uniform brightness distribution containing only bright areas (high brightness areas), while the first layer 11a has a non-uniform brightness distribution in which bright areas and dark areas (low brightness areas) are mixed together.
[0079] The first layer 11a has a more uneven brightness distribution compared to the second layer 11b. The method used to confirm this will be explained.
[0080] Let the thickness of the first layer 11a be t1, and the interface between the first layer 11a and other parts (in) Figure 4 , Figure 5 When indicated, the middle part of the first layer 11a is defined as the portion where the distance between the interface between the first layer 11a and the second layer 11b, and the interface between the first layer 11a and the coating layer 13, is greater than or equal to 0.1×t1.
[0081] When a first imaginary line parallel to the surface of the core 2 is drawn to the first layer 11a with a length of 1000 nm, passing through the middle portion of the thickness direction of the first layer 11a, and when it is drawn to the second layer 11b with a length of 1000 nm, the one in which high-brightness regions and low-brightness regions are observed alternately more often can be described as having a "more uneven brightness distribution". When a first imaginary line parallel to the surface of the core 2 is drawn to the first layer 11a with a length of 1000 nm, passing through the middle portion of the thickness direction of the first layer 11a, it is also possible that high-brightness regions and low-brightness regions are observed alternately more than twice along the first imaginary line. Furthermore, when the imaginary line cannot be drawn with a length of 1000 nm due to the small particle size of the soft magnetic metal particles 1, it is possible to set the particle size as r and draw the imaginary line with a length of r × π / 2 or more.
[0082] Figure 7 Line I shown is an example of a first imaginary line drawn through the middle portion of the thickness direction of the first layer 11a. Compared to the case where the first imaginary line is drawn parallel to the surface of the core 2 in the second layer 11b, the number of times high-brightness and low-brightness regions are observed alternately is significantly greater. Furthermore, high-brightness and low-brightness regions are observed alternately more than twice along the first imaginary line.
[0083] Furthermore, when a second imaginary line perpendicular to the first imaginary line is drawn towards the first layer 11a with a length corresponding to the thickness of the first layer 11a, high-brightness areas and low-brightness areas can be observed alternately more than twice along the second imaginary line. In this case, it can be stated more explicitly that the first layer 11a has a non-uniform brightness distribution.
[0084] Figure 7Line II shown is an example of the second imaginary line. The second imaginary line is perpendicular to the first imaginary line and is drawn with a length corresponding to the thickness of the first layer 11a, passing through the first layer 11a. Furthermore, high-brightness areas and low-brightness areas are observed alternately more than twice along the second imaginary line.
[0085] The length of the second imaginary line can be more than 0.8 times and less than 1 times the thickness of the first layer 11a.
[0086] There are no particular limitations regarding the reasons for the difference in brightness between the HAADF-STEM images of the first layer 11a and the second layer 11b. It could be due to differences in the composition of the first layer 11a and the second layer 11b. Specifically, it could be that, based on the number of atoms, the composition of the first layer 11a and the second layer 11b differs by more than 5%.
[0087] On the other hand, the reason for the difference in brightness between the high-brightness and low-brightness regions in the first layer 11a is unclear. The composition of the high-brightness and low-brightness regions can be substantially the same. That is, when comparing the composition of the high-brightness region with that of the low-brightness region without considering oxygen and carbon, if the difference in the proportion of each element in each region is less than 5% based on the number of atoms, the composition of each region can be considered the same.
[0088] The reason why high-brightness and low-brightness regions differ in brightness despite having essentially the same composition is unclear. It is believed that this difference is due to a density difference between the two regions. Specifically, this density difference results in a difference in the amount of electron rays transmitted between the high-brightness and low-brightness regions. This difference in electron ray transmission leads to the presence of regions with varying brightness within the HAADF-STEM image.
[0089] This could be achieved by setting the area ratio of the high-brightness region in the first layer 11a to S1 and the area ratio of the high-brightness region in the second layer 11b to S2, where S1 < S2. Alternatively, it could be S2 - S1 ≥ 0.01. Furthermore, it could be 0.02 ≤ S1 ≤ 0.98. Additionally, in... Figures 4-7 In the case represented by the diagram, S1 is in the range of 0.30 to 0.40, and S2 is 1. Binarization can be performed with S2 being 1 and S1 reaching its minimum value to determine the boundary between low-brightness and high-brightness regions, thus determining S1. The observation conditions for HAADF-STEM images are arbitrary. The magnification can be 1,000,000 times, and the resolution can be 1000 pixels / nm. 2 above.
[0090] There are no particular restrictions on the proportion of "soft magnetic metal particles in the first layer 11a having a more uneven brightness distribution than the second layer 11b" relative to all the soft magnetic metal particles contained in the soft magnetic metal powder. Whether each soft magnetic metal particle has an uneven brightness distribution can be determined by observing the cross-section of each soft magnetic metal particle contained in the soft magnetic metal powder. Furthermore, the proportion of soft magnetic metal particles with uneven brightness distribution in the soft magnetic metal powder need to be 10% or more, based on the number of particles.
[0091] There are no particular limitations on the thickness of the oxide layer 11; for example, it can be less than 200 nm or more than 1 nm but less than 100 nm. There are no particular limitations on the thickness of the first layer 11a; for example, it can be more than 1 nm but less than 100 nm. There are no particular limitations on the thickness of the second layer 11b; for example, it can be more than 1 nm but less than 20 nm.
[0092] In addition to the oxide layer 11, the coating portion 10 of the soft magnetic metal particle 1 may also have a coating layer 13 in contact with the surface of the oxide layer 11. There are no particular limitations on the composition of the coating layer 13. For example, the coating layer 13 can be formed by glass coating, a technique commonly practiced in this art. For example, the coating layer 13 may contain phosphate glass or silica glass.
[0093] When the soft magnetic metal particles 1 have a coating layer 13, the voltage resistance can be further improved.
[0094] The following describes the method for manufacturing the soft magnetic metal powder according to this embodiment.
[0095] First, prepare a soft magnetic metal powder containing soft magnetic metal particles, which will ultimately form the core 2. There are no particular restrictions on the method for preparing the soft magnetic metal powder. For example, commercially available soft magnetic metal powder can be prepared, or it can be produced by atomization methods such as water atomization or gas atomization.
[0096] Whether the soft magnetic metal powder obtained by atomization has an amorphous or crystalline structure is mainly determined by the composition of the soft magnetic metal powder.
[0097] When soft magnetic metal powder obtained by atomization has an amorphous structure, heat treatment can sometimes precipitate nanocrystals with a particle size of 5 nm to 50 nm, resulting in soft magnetic metal powder with a nanocrystal structure. Whether nanocrystals can be precipitated through heat treatment is mainly determined by the composition of the soft magnetic metal powder.
[0098] Regarding heat treatment conditions, for example, the temperature should be above 450°C and below 650°C for at least 1 minute and less than 180 minutes. Furthermore, typically, a single soft magnetic metal particle contains multiple nanocrystals. That is, the particle size of the soft magnetic metal particle is different from the crystal size of the nanocrystals. Moreover, the crystal structure of the soft magnetic metal powder can be confirmed using XRD or transmission electron microscopy. When the soft magnetic metal powder contains nanocrystals, the final magnetic core's Hc is more likely to decrease, and the relative permeability is more likely to increase.
[0099] The average particle size of soft magnetic metal powder can be adjusted by changing the atomization conditions. Alternatively, it can be adjusted by grading. Furthermore, the average particle size can be adjusted by blending multiple soft magnetic metal powders with different average particle sizes.
[0100] Next, a coating portion of the soft magnetic metal particles contained in the soft magnetic metal powder is made.
[0101] There are no particular limitations on the method for forming an oxide layer on the surface of the core. For example, the surface of the soft magnetic metal particles can be oxidized by heat treatment in an oxygen-containing atmosphere. First, when a second layer with a relatively uniform brightness distribution in the HAADF-STEM image is formed on the surface of the core, there are no particular limitations on the oxygen concentration in the atmosphere. For example, it can be 100 ppm to 10000 ppm. There are no particular limitations on the heat treatment temperature, for example, it can be 250°C to 450°C. There are no particular limitations on the heat treatment time, for example, it can be 0.5 hours to 10 hours. The higher the oxygen concentration, the higher the heat treatment temperature, and the longer the heat treatment time, the easier it is to thicken the second layer.
[0102] Next, a first layer with relatively uneven brightness distribution in the HAADF-STEM image is formed on the surface of the second layer.
[0103] There are no particular limitations on the method for forming the first layer. For example, one method is to oxidize soft magnetic metal powder by placing it in a high-temperature and high-humidity atmosphere. There are no particular limitations on the temperature, for example, it can be 50°C to 95°C. There are no particular limitations on the humidity, for example, it can be 60% to 90%. There are no particular limitations on the processing time, for example, it can be 1 hour to 1000 hours.
[0104] When soft magnetic metal particles contain Fe and Si, the second layer formed through heat treatment tends to contain oxides of both Fe and Si. Conversely, in the first layer formed under high temperature and high humidity, Fe oxides are more likely to be present than Si oxides. This is because, when forming an oxide layer under high temperature and high humidity, Fe oxidizes more readily than Si, and the more easily oxidized element moves to the surface.
[0105] The boundary between the first and second layers can be determined using bright-field images obtained through STEM. Alternatively, the boundary can be determined by measuring a line profile from the core towards the surface of the soft magnetic metal particles and confirming the brightness variations within the line profile. For example, the inflection points of the line profile can be set as the boundary.
[0106] There are no particular restrictions on the coating method used when creating the coating layer; methods commonly used in this technical field can be employed.
[0107] For example, dry coating can be performed. There are no particular restrictions on the type of coating layer at this time. For example, a coating layer composed of phosphate-based glass can be formed. In this case, it can be achieved by using... Figure 8 The powder coating apparatus 100 shown forms a coating layer by mechanical fusion (mechanical alloying).
[0108] A mixture 50 is prepared by mixing phosphate-based glass powder into a soft magnetic metal powder that has formed an oxide layer. By rotating a rotor 101 in this state, the mixture 50 is compressed between a pressure head 102 and the inner wall of the rotor 101, generating friction and thus heat. Due to this frictional heat, the phosphate-based glass softens, and due to the compression, it is fixed to the surface of the oxide layer, which is then cooled to form a coating.
[0109] For example, wet coating can also be performed. There are no particular restrictions on the type of coating layer at this time. For example, a coating layer composed of Si oxide can be prepared by using the sol-gel method of TEOS.
[0110] There are no particular restrictions on the magnetic powder used in the fabrication of the magnetic core. The aforementioned soft magnetic metal powder can be used directly as the magnetic powder, or it can be prepared by mixing the aforementioned soft magnetic metal powder with other powders.
[0111] The obtained magnetic powder is then molded to obtain a magnetic core. There are no particular limitations on the molding method. As an example, a method for obtaining a magnetic core by pressure molding will be described.
[0112] First, the magnetic powder is mixed with the resin. By mixing the resin, a high-strength molded body can be easily obtained through molding. There are no particular restrictions on the type of resin. For example, phenolic resin and epoxy resin can be used. There are also no particular restrictions on the amount of resin added. When adding resin, it can be added at more than 1% by mass and less than 5% by mass relative to the magnetic powder.
[0113] Granulated powder is obtained by granulating a mixture of magnetic powder and resin. There are no particular limitations on the granulation method. For example, a stirrer can be used for granulation. There are no particular limitations on the particle size of the granulated powder.
[0114] The obtained granulated powder is pressurized to form a molded body. There are no particular limitations on the molding pressure; for example, it can be set to a surface pressure of 1 ton / cm². 2 Above and 10 tons / cm 2 The higher the molding pressure, the easier it is to increase the relative permeability, but the lower the voltage withstand capability.
[0115] Here, when the oxide layer 11 includes the first layer 11a and the second layer 11b described above, even if the molding pressure is increased, the withstand voltage is difficult to decrease. That is, by increasing the molding pressure, the relative permeability can be easily increased while maintaining a high withstand voltage.
[0116] Then, the resin contained in the molded body is cured to obtain a magnetic core. There are no particular restrictions on the curing method; heat treatment can be performed under conditions that allow the resin used to cure.
[0117] There are no particular limitations on the application of the magnetic core. For example, it is suitable for use as a magnetic core for inductors, especially for power inductors. Moreover, it is also suitable for use in inductors in which the magnetic core and coil are integrally formed.
[0118] Furthermore, the aforementioned magnetic core or magnetic components using the aforementioned magnetic core can be well applied to electronic devices.
[0119] In particular, because the aforementioned magnetic cores have high voltage withstand capability and small voltage tolerance deviation, they are suitable for applications requiring miniaturization, lightweight design, and high reliability. For example, they are suitable for use in magnetic cores, magnetic components, and electronic devices in hybrid electric vehicles, plug-in hybrid electric vehicles, and electric vehicles.
[0120] Example
[0121] The present invention will now be described in detail based on specific embodiments.
[0122] (Experimental Example 1)
[0123] Soft magnetic metal powders with compositions shown in the "Core Composition" column of Table 1 are prepared. Specifically, ingots of various materials are prepared as raw material metals to obtain molten metal with the target composition, and weighed. Then, after evacuating the chamber, the crucible is heated by high-frequency induction using a working coil located outside the crucible to melt and mix the raw material metals in the crucible, obtaining molten metal (molten liquid) at 1400°C to 1600°C.
[0124] The obtained molten liquid is supplied to the chamber in a continuous linear flow through a nozzle located at the bottom of the crucible. Gas is blown onto the supplied molten liquid to obtain powder. The gas injection temperature is set to 20°C.
[0125] In samples 17-20, the obtained powders were heat-treated at 550°C for 60 minutes in an inert atmosphere (N2 gas). In samples 21-24, the obtained powders were heat-treated at 600°C for 60 minutes in an inert atmosphere (N2 gas).
[0126] The obtained powder was classified using a sieve. The classification process resulted in an average particle size of approximately 25 μm.
[0127] ICP analysis confirmed that the composition of the molten metal was approximately consistent with that of the soft magnetic metal powder. Furthermore, the compositions of samples 1-4 (atomic ratio) were 88.0Fe–12.0Si; samples 5-8 (atomic ratio) were 72.7Fe–11.6Si–10.8B–2.2Cr–2.7C; samples 9-12 (atomic ratio) were 63.2Fe–15.8Co–10.0B–5.0P–5.0Si–1.0Cr; samples 13-16 (atomic ratio) were 62.5Fe–21.0Co–11.0B–4.0P–0.5Si–1.0C; and samples 17-20 (atomic ratio) were 73.5Fe–13.5Si–9.0B–3.0Nb–1.0Cu. The composition of samples 21 to 24, in terms of atomic ratio, is 79.0Fe-1.0Si-10.0B-7.0Nb-3.0P.
[0128] In this embodiment, the composition is described entirely in terms of atomic ratios.
[0129] The fine structure of each soft magnetic metal powder was confirmed by XRD. It was confirmed that: samples 1-4 have a crystalline structure, samples 5-16 have an amorphous structure, and samples 17-24 have a nanocrystalline structure. In the tables below, samples marked "crystalline" in the fine structure column have a crystalline structure. Samples marked "amorphous" have an amorphous structure. Samples marked "nanocrystalline" have a nanocrystalline structure.
[0130] Then, an oxide layer is formed on the obtained powder.
[0131] For the sample described as "High Heat 2" in the "Second Layer Formation Treatment" column, a heat treatment at 300°C for 1 hour was performed to form the oxide layer corresponding to the second layer in each embodiment. At this time, the oxygen concentration in the atmosphere was made to be 500 ppm.
[0132] On the oxide layer corresponding to the second layer in each embodiment, an oxide layer corresponding to the first layer in each embodiment is formed. The sample labeled "High Heat 1" in the "First Layer Formation Treatment" column is heat-treated at 350°C for 1 hour. During this time, the oxygen concentration in the atmosphere is set to 1000 ppm. That is, the heat treatment conditions corresponding to "High Heat 1" are heat treatment conditions that facilitate oxidation more easily than the heat treatment conditions corresponding to "High Heat 2". The sample labeled "High Humidity" in the "First Layer Formation Treatment" column is placed in an environment with a temperature of 85°C and a humidity of 85% for 5 hours.
[0133] Next, a cylindrical magnetic core was fabricated using the obtained soft magnetic metal powder.
[0134] (Withstand voltage V under low applied voltage) L (determination)
[0135] Soft magnetic metal powder was mixed with resin (phenolic resin). The mixture was prepared at a resin content of 3% by mass. Next, granulation was performed using a standard planetary mixer to obtain granulated powder with a particle size of approximately 500 μm. The obtained granulated powder was then subjected to a surface pressure of 4 tons / cm². 2 Pressure molding is performed to obtain a cylindrical molded body with a diameter of 8.0 mmφ and a height of 8.0 mm. The obtained molded bodies are then cured at a temperature of 150°C to obtain a cylindrical magnetic core.
[0136] Twenty cylindrical magnetic cores were fabricated for each sample. In-Ga electrodes were formed on two faces of each cylindrical magnetic core perpendicular to the thickness direction. Next, a voltage was applied using a source meter (THK-2011ADMPT) to measure the voltage when a current of 1 mA flowed. The withstand voltage of the cylindrical magnetic core was then measured by dividing this voltage by the thickness of the cylindrical magnetic core. The average withstand voltage of the 20 cylindrical magnetic cores was taken as the Vt value for each sample. L .
[0137] (Voltage withstand voltage under high pressure) H (determination)
[0138] In addition to setting the surface pressure to 8 tons / cm 2 In addition, with V L Determine V under the same conditions H .
[0139] (Calculate the rate of decrease in withstand voltage as pressure increases)
[0140] Regarding the reduction rate of withstand voltage, via 1 - (V H / V L Calculated. A reduction rate below 24% is considered good, and below 16% is considered even better.
[0141] (Thickness of each layer)
[0142] HAADF-STEM images are obtained by observing the cross-section of the soft magnetic metal particles in each sample using STEM.
[0143] First, soft magnetic metal powder is fixed onto a Cu conductive tape. Next, a Pt sputtered film is fabricated by sputtering, achieving a thickness of approximately 20 nm.
[0144] Next, the soft magnetic metal powder fixed on the Cu conductive tape was placed into a Hitachi High-Tech NX5000 focused ion beam probe. The fixed soft magnetic metal powder was observed, and soft magnetic metal particles with the same average particle size as the powder were selected. A Pt deposition film with a thickness of approximately 100 nm was then fabricated on this film using electron beam deposition. On top of this, a Pt deposition film with a thickness of approximately 2 μm was fabricated using ion beam deposition.
[0145] Then, microsamples with a width of 10 μm, a height of 10 μm, and a thickness of 1 μm were cut from soft magnetic metal particles having the same average particle size as the soft magnetic metal powder, with the surface of the soft magnetic metal particles included, and fixed on a Mo grid. Next, thinning was performed using FIB until a thickness of 30 nm was achieved. Furthermore, HAADF-STEM images were captured using a STEM with spherical aberration correction. The magnification of the HAADF-STEM images was set to 2.5 million times.
[0146] The measurement site was set near the surface of the soft magnetic metal particles, and the thickness of each layer was measured to obtain the measured value of each layer thickness. The same measurement was performed on 10 soft magnetic metal particles, and the obtained measured values were averaged to calculate the thickness of each layer. In the embodiments of Experimental Example 1, namely sample numbers 4, 8, 12, 16, 20, and 24, the thickness of the oxide layer (the combined thickness of the first and second layers) was confirmed to be approximately 50 nm. In the embodiments described below, unless otherwise specified, the thickness of the oxide layer was also confirmed to be approximately 50 nm.
[0147] (Determination of S1 and S2 and presence or absence of a non-uniform oxide layer)
[0148] S1 and S2 were measured when the soft magnetic metal particles had an oxide layer. Specifically, the HAADF-STEM image obtained by observing the oxide layer was binarized into high-brightness and low-brightness portions. In each example (sample numbers 4, 8, 12, 16, 20, and 24), the difference between the first and second layers could be clearly seen through binarization. Furthermore, S1 and S2 were calculated from the image obtained through binarization. In the examples described below, unless otherwise specified, S1 = 0.15 or more and 0.50 or less, and S2 = 1.
[0149] In contrast, in each comparative example, the HADDF-STEM image obtained by observing the oxide layer could not be binarized based on the difference in brightness.
[0150] Furthermore, for HAADF-STEM images, a first imaginary line of 1000 nm in length, parallel to the surface of the core, is drawn in the middle of the first layer. Additionally, a second imaginary line, perpendicular to the first imaginary line and corresponding in length to the thickness of the first layer, is drawn inside the first layer. In various embodiments, high-brightness regions and low-brightness regions are observed alternately more than twice along the first imaginary line. Furthermore, high-brightness regions and low-brightness regions are observed alternately more than twice along the second imaginary line. In contrast, even when an imaginary line is drawn in the middle of the second layer, only high-brightness regions can be observed along that line.
[0151] As described above, it was confirmed that in each embodiment, S1 < S2 is satisfied, and a first layer with a non-uniform brightness distribution of the oxide layer compared to the second layer is also present. Similarly, in the embodiments following Experimental Example 2, it was also confirmed that S1 < S2 is satisfied, and a first layer with a non-uniform brightness distribution of the oxide layer compared to the second layer is also present.
[0152] Table 1
[0153]
[0154] As shown in Table 1, in each embodiment, the oxide layer has a first layer with a more uneven brightness distribution than the second layer, satisfying S1 < S2. Furthermore, in embodiments satisfying 0.02 ≤ S1 ≤ 0.98, the rate of decrease in withstand voltage with increasing pressure is lower. In contrast, in the comparative examples, the rate of decrease in withstand voltage with increasing pressure is higher.
[0155] (Experimental Example 2)
[0156] For samples numbered 4, 8, 12, 16, 20, and 24, the humidity of the atmosphere during the first layer formation process was varied between 50% and 85%, and the processing time for the first layer formation process was varied between 1 hour and 24 hours. Higher humidity tended to result in a smaller S1 value and a larger oxide layer thickness. Longer processing times also tended to result in a smaller S1 value and a larger oxide layer thickness. Using these characteristics, the oxide layer thickness was set to approximately 50 nm, and the S1 value was varied. The results are shown in Table 2.
[0157] Table 2
[0158]
[0159] As shown in Table 2, in each embodiment, even with changes in S1, the rate of decrease in withstand voltage accompanying the increase in applied pressure is reduced. In particular, the rate of decrease in withstand voltage is reduced when S1 is 0.10 or higher and 0.80 or lower.
[0160] (Experimental Example 3)
[0161] For sample number 12, the thickness of the oxide layer (the thickness of the first layer) was varied by changing the processing time during the first layer formation process between 0.1 hours and 24 hours. The results are shown in Table 3.
[0162] Table 3
[0163]
[0164] As shown in Table 3, in each embodiment, even with changes in the thickness of the oxide layer, the rate of decrease in withstand voltage with increasing applied pressure decreased. It was also confirmed that in each embodiment of Experimental Example 3, the oxide layer consisted of a second layer with a thickness of 2 nm and a first layer (the first layer being a non-uniform oxide layer). In particular, when the thickness of the first layer (the non-uniform oxide layer) was 8 nm or more, the rate of decrease in withstand voltage with increasing applied pressure was especially low.
[0165] (Experimental Example 4)
[0166] The soft magnetic metal powders shown in Tables 4A and 4B before coating were coated to form a coating layer, thereby producing samples numbered 59 to 82.
[0167] (Dry coating (phosphate coating))
[0168] Phosphate-based glass (P-Zn-Al-O oxide glass) was added together with soft magnetic metal powder. Figure 7In the powder coating apparatus shown, the thickness of the coating layer is controlled to approximately 20 nm by controlling the amount of phosphate-based glass added, thereby forming a coating layer composed of phosphate-based glass. The results are shown in Tables 4A and 4B.
[0169] (Wet coating (Si coating))
[0170] A coating layer consisting of Si oxides was formed on soft magnetic metal powder using the sol-gel method with TEOS. The coating thickness was controlled to approximately 20 nm by adjusting the TEOS concentration. The results are shown in Tables 4A and 4B.
[0171] Table 4A
[0172]
[0173] Table 4B
[0174]
[0175] As shown in Table 4, in each embodiment, even with the formation of a coating layer, the rate of decrease in withstand voltage with increasing pressure is reduced.
[0176] (Experimental Example 5)
[0177] For samples 67 and 69, the procedures were performed under the same conditions, except for changing the average particle size of the soft magnetic metal powder. The results are shown in Table 6. Furthermore, when the average particle size of the soft magnetic metal powder was 1 μm to 10 μm, the soft magnetic metal particles were embedded in resin and cured before micro-sample cutting was performed. Specifically, the soft magnetic metal particles were fixed on a Mo grid, and micro-sample cutting was performed. Other aspects were the same as when the particle size of the soft magnetic metal particles was 25 μm.
[0178] Table 5
[0179]
[0180] As shown in Table 5, in each embodiment, even with changes in the average particle size, the rate of decrease in withstand voltage accompanying the increase in applied pressure is reduced.
[0181] (Experimental Example 6)
[0182] Except for altering the composition (core composition) of the soft magnetic metal powder, samples 91-110 were performed in the same manner as samples 2 and 4. In samples 91 and 92, the soft magnetic metal powder composition was essentially Fe-only. In samples 93 and 94, the atomic ratio was 55.0Fe–45.0Ni. In samples 95 and 96, the atomic ratio was 89.4Fe–8.6Si–2.0Cr. In samples 97 and 98, the atomic ratio was 73.7Fe–16.4Si–9.9Al. In samples 99 and 100, the atomic ratio was 78.1Fe–11.0Si–10.0Al–0.9Ni. In samples 101 and 102, the atomic ratio was 49.2Fe–42.0Ni–4.0Si–4.8Co. For samples 103 and 104, the atomic ratio is set as 50.0Fe–50.0Co. For samples 105 and 106, the atomic ratio is set as 49.0Fe–49.0Co–2.0V. For samples 107 and 108, the atomic ratio is set as 83.6Fe–4.4Co–12.0Si. For samples 109 and 110, the atomic ratio is set as 66.3Fe–7.4Co–16.4Si–9.9Al. The results are shown in Table 6A.
[0183] Except for altering the composition (core composition) of the soft magnetic metal powder, samples 111 to 122 were performed in the same manner as samples 6, 8, 10, 12, 14, and 16. In samples 111 and 112, the atomic ratio was set to 81.6Fe–3.4Si–13.4B–1.6C. In samples 115 and 116, the atomic ratio was set to 72.3Fe–18.2Si–9.5B. In samples 117 and 118, the atomic ratio was set to 56.0Fe–24.0Co–15.0P–5.0C. In samples 119 and 120, the atomic ratio was set to 56.0Fe–24.0Co–20.0B. In samples 121 and 122, the atomic ratio was set to 56.0Fe–24.0Co–15.0B–5.0Si. The results are shown in Table 6B.
[0184] Except for altering the composition (core composition) of the soft magnetic metal powder, samples 123–126 were performed in the same manner as samples 18, 20, 22, and 24. In samples 123 and 124, the atomic ratio was set as 63.2Fe–15.8Co–11.0B–9.0P–1.0Si. In samples 125 and 126, the atomic ratio was set as 63.2Fe–15.8Co–10.0B–5.0P–5.0Si–1.0Cr. The results are shown in Table 6C.
[0185] Table 6A
[0186]
[0187] Table 6B
[0188]
[0189] Table 6C
[0190]
[0191] According to Tables 6A to 6C, in each embodiment, even if the composition of the soft magnetic metal powder is changed, the rate of decrease in withstand voltage accompanying the increase in applied pressure is reduced.
[0192] [Symbol Explanation]
[0193] 1: Soft magnetic metal particles
[0194] 2: Core
[0195] 10: Covering part
[0196] 11: Oxide layer
[0197] 11a: First layer
[0198] 11b: Second layer
[0199] 13: Coating layer
[0200] 50: Mixture
[0201] 100: Powder coating device
[0202] 101: Rotor
[0203] 102: Pressure head.
Claims
1. A soft magnetic metal powder, wherein, Contains: soft magnetic metal particles with a core and a coating. The soft magnetic metal particles contain Fe. The coating portion has an oxide layer that contacts the surface of the core portion. The oxide layer has a second layer in contact with the surface of the core and a first layer in contact with the second layer. The first and second layers contain oxides of the elements contained in the core. When the cross-section of the soft magnetic metal particles was observed using HAADF-STEM, the first layer showed a more uneven brightness distribution compared to the second layer.
2. The soft magnetic metal powder as described in claim 1, wherein, When the image obtained by observing the cross-section of the soft magnetic metal particles using HAADF-STEM is binarized into high-brightness and low-brightness regions, When the area ratio of the high-brightness region in the first layer is set to S1 and the area ratio of the high-brightness region in the second layer is set to S2, S1 < S2.
3. The soft magnetic metal powder as described in claim 2, wherein, It satisfies 0.02≤S1≤0.
98.
4. The soft magnetic metal powder according to any one of claims 1 to 3, wherein, The thickness of the oxide layer is less than 200 nm.
5. The soft magnetic metal powder according to any one of claims 1 to 3, wherein, The covering portion has a coating layer that contacts the surface of the oxide layer.
6. A magnetic core, wherein, It comprises the soft magnetic metal powder according to any one of claims 1 to 5.
7. A magnetic component, wherein, It comprises the soft magnetic metal powder according to any one of claims 1 to 5.
8. An electronic device, wherein, It comprises the soft magnetic metal powder according to any one of claims 1 to 5.
Citation Information
Patent Citations
Composite magnetic material, core using the same, and magnetic element
JP2004197218A
Complex magnetic material and method for manufacturing inductor using the same
JP2004363466A